Carbon Storage Potential of Eucalyptus Tereticornis Plantations - Ulman, Yashmita; Avudainayagam, S. (Indian Forester, 2014)
The carbon storage potential of Eucalyptus tereticornis plantations (one to four years old) was estimated using two different methods. The carbon concentration in different parts of the tree for all aged plantation was found in decreasing order: stem > root > branch > leaf. Carbon content of litter showed that the lowest return was from the -1 youngest and highest return was from the oldest stand. The carbon content was found to be 38.10 t ha (one year -1 plantation) and 115.88 t ha (four year plantation) when estimated by biomass and carbon content per cent (formula -1 -1 method) and it was found to be 42.66 t ha (one year plantation)and 129.04 t ha (four year plantation)when estimated by the assumption that carbon fractions is fifty per cent of biomass (assumption method). The results showed that the assumption method leads to an over-estimation of carbon content for the total organic carbon of the same age when compared to the formula method (especially for younger aged plantations).